PC / PBT alloy material with high chemical resistance and preparation method thereof
By adding hexagonal boron nitride nanotubes to the PC/PBT alloy material and radiated to form a crosslinking network structure, the problem of insufficient resistance to the traditional PC/PBT alloy material is solved, and its tolerance in harsh chemical environments is significantly improved.
Patent Information
- Application Number
- CN202411926652.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Traditional PC/PBT alloy materials have insufficient chemical resistance when facing highly corrosive chemicals, which may lead to stress traces, cracks or cracks, and are particularly poor in applications in aerospace and energy fields.
Hexagonal boron nitride nanotubes are added to the PC/PBT alloy system, and the molecular chain reaction is excited by radiation treatment to form a crosslinking network structure and chemical connections to improve the compatibility and chemical resistance of the material.
It significantly improves the overall chemical resistance of PC/PBT alloy materials, can better resist erosion from harsh chemical environments such as acid and alkali, organic solvents, extend the material life and improve safety.
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite material processing, and in particular to a PC / PBT alloy material with high chemical resistance and a preparation method thereof. Background Art
[0002] PC / PBT alloy material is an engineering plastic composed of PC and PBT. It combines the toughness and excellent dimensional stability of PC with the rigidity, excellent heat resistance and chemical corrosion resistance of PBT. This alloy material has high surface hardness and excellent mechanical properties. It can also resist high-temperature deformation and stress cracking. Therefore, it has been widely used in many fields such as automobile manufacturing and electronic equipment. However, the chemical corrosion resistance of traditional PC / PBT alloys has certain limitations. When exposed to certain highly corrosive chemicals or specific organic solvents, the finished products may have problems such as stress marks, cracking or even cracking, especially when it is necessary to spray highly corrosive exterior paint. This situation is more obvious.
[0003] The common chemical-resistant PC / PBT alloy materials currently developed on the market can meet the requirements of chemical resistance to a certain extent when dealing with commonly used cleaners and detergents in life scenes, but their performance is still insufficient when used in high-end fields such as aerospace and energy. For example, in the aerospace field, some special fuels, lubricants and other chemicals, as well as highly corrosive detergents used during cleaning and maintenance, may corrode PC / PBT alloy materials, causing material performance degradation, and thus affecting the life and safety of components. In the energy field, chemical substances such as battery electrolytes and insulating oils are highly corrosive to materials. After long-term contact, PC / PBT alloy materials may swell, embrittle, and other phenomena, reducing the reliability of the equipment. Therefore, the development of highly chemical-resistant PC / PBT alloy materials is of great significance for promoting their application in high-end fields such as aerospace and energy. Summary of the invention
[0004] In view of the limitations of current technology, the present invention proposes a PC / PBT alloy material with high chemical resistance. By adding hexagonal boron nitride nanotubes to the PC / PBT alloy system and irradiating the alloy material, the following effects are achieved: on the one hand, the radiation treatment can stimulate the PC and PBT molecular chains to produce a large number of active free radicals, which trigger reactions between the molecular chains, thereby strengthening the chemical connection between PC and PBT and forming an interconnected network structure; on the other hand, the radiation treatment will also increase the surface activity of the hexagonal boron nitride nanotubes and easily react with the active groups on PC / PBT, thereby improving the compatibility between the organic matrix and the inorganic matter in the system. Since the hexagonal boron nitride nanotubes themselves have a planar hexagonal mesh structure, they will be entangled with the molecular chain as it moves, thereby playing a role of firm anchoring. The cross-linked structure between the PC and PBT molecular chains and the anchoring effect of the hexagonal boron nitride nanotubes work together to limit the movement of the PC / PBT molecular chains. At the same time, hexagonal boron nitride nanotubes further increase the complexity of the chemical penetration path, reduce the exposure of carbonate groups to adverse chemical environments, and make the alloy material difficult to be destroyed and dissolved when faced with corrosive substances, thereby significantly improving its overall chemical resistance. The high chemical resistance PC / PBT alloy material provided has good tolerance to harsh chemical environments such as acids, alkalis, and organic solvents, so it has broad application scenarios in high-end fields such as aerospace and energy.
[0005] A PC / PBT alloy material with high chemical resistance, characterized in that it comprises the following raw material components in parts by mass: PC resin: 55-80 parts PBT resin: 20-45 parts Compatibility agent: 1-5 parts Ester exchange inhibitor: 0.1-1 part Toughening agent: 1-10 parts Inorganic nanopowder: 1-5 parts Antioxidant: 0.1-1 part Lubricant: 0.2-1 part The PC resin is bisphenol A polycarbonate, and its melt flow index is 10-20 g / min under the test conditions of 300° C. / 1.2 kg.
[0006] The intrinsic viscosity of the PBT resin is 0.8-1.2 dL / g.
[0007] The compatibilizer is an ethylene-methyl acrylate-glycidyl methacrylate terpolymer.
[0008] The transesterification inhibitor is one or more of trimethyl phosphate, triphenyl phosphate, and diphenyl isooctyl phosphate, preferably triphenyl phosphate.
[0009] The toughening agent is MBS resin, and the core of the core-shell structure is styrene-butadiene rubber, and the shell is a copolymer of styrene and methyl methacrylate.
[0010] The inorganic nano powder is hexagonal boron nitride nanotube.
[0011] The antioxidant is one or more of 1010, 1076 and 168.
[0012] The lubricant is one or more of pentaerythritol stearate, calcium stearate and stearic acid amide.
[0013] In addition, the present invention also provides a method for preparing a PC / PBT alloy material with high chemical resistance, wherein the preparation steps include preparing the PC / PBT alloy material and irradiating it.
[0014] The preparation of the PC / PBT alloy material is to stir and mix PC resin, PBT resin, compatibilizer, ester exchange inhibitor, toughening agent, inorganic nano powder, antioxidant and lubricant at high speed, add the mixture to the feeding port of a twin-screw extruder, melt extrude and granulate, the temperature of each section of the extruder is 240-270°C, the screw speed is 300-400rpm, and the screw aspect ratio is 40:1.
[0015] The radiation treatment is to irradiate the PC / PBT alloy material with an electron beam generated by a high-energy accelerator, with a radiation dose of 50-200 kGy.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1) By irradiating the PC / PBT alloy material, the compatibility between PC and PBT is effectively improved, which promotes the formation of an interconnected network structure between the molecular chains.
[0017] 2) Hexagonal boron nitride nanotubes are introduced into the PC / PBT alloy system and chemically connected to the matrix resin through radiation treatment. The special planar hexagonal network structure of hexagonal boron nitride nanotubes forms a strong anchoring effect between it and the PC / PBT alloy material.
[0018] 3) The cross-linked structure between the PC and PBT molecular chains and the anchoring effect of the hexagonal boron nitride nanotubes work together to effectively limit the movement of the molecular chains. This structural feature reduces the chance of carbonate groups in the PC / PBT alloy being exposed to adverse chemical environments, making them difficult to be destroyed and dissolved when exposed to corrosive substances, thereby significantly improving the overall chemical resistance of the material. DETAILED DESCRIPTION
[0019] The following specific examples are provided to further illustrate the substantive content of the present invention. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0020] The raw material compositions of Examples 1-5 are in parts by mass, as shown in Table 1, and the preparation methods are as follows: Firstly, a PC / PBT alloy material is prepared, PC resin, PBT resin, a compatibilizer, an ester exchange inhibitor, a toughening agent, hexagonal boron nitride carbon nanotubes, an antioxidant and a lubricant are uniformly mixed by high-speed stirring, and the mixture is added to the feeding port of a twin-screw extruder, and melt-extruded into granules. During extrusion, the temperature of each section of the extruder is 240-270°C, the screw speed is 300-400rpm, and the screw aspect ratio is 40:1.
[0021] Then, the PC / PBT alloy material is irradiated by an electron beam generated by a high-energy accelerator, and the radiation dose is shown in Table 1.
[0022] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 Example 4 Example 5 PC 60 60 60 60 60 60 60 60 60 60 PBT 35 35 35 35 35 35 35 35 35 35 Ethylene-methyl acrylate-glycidyl methacrylate 2 2 2 2 2 2 2 2 2 2 Triphenyl phosphate 2 2 2 2 2 2 2 2 2 - Diphenyl 2-ethylhexyl phosphate - - - - - - - - - 2 MBS 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 <![CDATA[Nano SiO 2 > - 2.5 - - - - - - - - Carbon Nanotubes - - - - 2.5 - - - - - Hexagonal Boron Nitride Nanotubes - - 2.5 - - 2.5 2.5 2.5 3.5 2.5 1010 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 168 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 Pentaerythritol stearate 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 Radiation dose (kGy) 0 0 0 50 50 200 150 50 150 200 The preparation methods of PC / PBT alloy materials in Comparative Examples 1-5 are exactly the same as those in Examples 1-5, but there are the following differences: Comparative Example 1 is not subjected to radiation treatment; Comparative Example 2 adds nano-SiO 2 , and the sample was not irradiated; in comparative example 3, hexagonal boron nitride nanotubes were added, but the sample was also not irradiated; in comparative example 4, no inorganic nanopowder was added for modification, and only 50kGy irradiation treatment was performed; in comparative example 5, carbon nanotubes were added, and 50kGy irradiation treatment was performed.
[0023] The samples prepared in the above embodiments and comparative examples were tested, and the test data are listed in Table 2.
[0024] The tensile strength is tested according to GB / T 1040.2; the flexural strength is tested according to GB / T 9341; and the cantilever beam notched impact strength is tested according to GB / T 1843.
[0025] In order to evaluate the chemical resistance of PC / PBT alloy materials, immersion tests were carried out according to the requirements of GB / T 11547. 10% sulfuric acid solution was selected to evaluate the resistance of the material in an acidic environment; 10% NaOH solution was used to evaluate the resistance of the material in an alkaline environment, and toluene and acetone were used to test the stability of the material in organic solvents. Immersion conditions: room temperature, time 5 minutes. The test values of the samples after immersion in different solutions were compared with the values before immersion. The higher the performance retention rate, the better the chemical resistance of the material. During the test, 5 specimens were taken from each group to calculate the average value. The tensile strength percentages after immersion in 10% sulfuric acid, 10% sodium hydroxide, toluene and acetone solutions are represented by T1, T2, T3 and T4, respectively, the bending strength percentages are represented by F1, F2, F3 and F4, respectively, and the Izod notched impact strength percentages are represented by N1, N2, N3 and N4, respectively.
[0026] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 Example 4 Example 5 Tensile strength (MPa) (unsoaked) 54 56 57 60 62.5 73 69 65 74 78 Tensile strength (MPa) (immersed in 10% sulfuric acid) 28 30 31 33 35 58 51 44 62 59 T1(%) 52 54 54 55 56 79 74 68 84 76 Tensile strength (MPa) (immersed in 10% sodium hydroxide) 24 26 30 33 35 53 47 41 58 55 T2(%) 44 46 53 55 56 73 68 63 78 71 Tensile strength (MPa) (immersed in toluene) 23 26 27 29 30 44 39 34 46 46 T3(%) 43 46 47 48 48 60 57 52 62 59 Tensile strength (MPa) (immersion in acetone) 32 35 37 40 43 61 54 48 66 61 T4(%) 59 63 65 67 69 84 78 74 89 78 Flexural strength (MPa) (unimmersed) 80 83 84 87 90 108 99 95 110 110 Flexural strength (MPa) (immersed in 10% sulfuric acid) 37 42 45 48 50 84 71 63 92 80 F2(%) 46 51 54 55 56 78 72 66 84 73 Flexural strength (MPa) (immersed in 10% sodium hydroxide) 32 37 38 44 47 81 67 59 90 79 F1(%) 40 45 45 51 52 75 68 62 82 72 Flexural strength (MPa) (immersed in toluene) 40 42 45 49 51 80 69 62 86 78 F3(%) 50 51 54 56 57 74 70 65 78 71 Flexural strength (MPa) (immersed in acetone) 32 36 37 41 47 75 62 54 83 73 F4(%) 40 43 44 47 52 69 63 57 75 66 <![CDATA[Izod impact strength of cantilever beam (kJ / m 2 )(not immersed)]]> 55 56 58 53 55 54 57 60 58 55 <![CDATA[Izod impact strength of cantilever beam (kJ / m 2 )(immersed in 10% sulfuric acid)]]> 28 30 32 30 32 37 38 37 41 35 N1(%) 51 54 55 57 58 69 67 62 71 64 <![CDATA[Izod impact strength of cantilever beam (kJ / m 2 )(soaked in 10% sodium hydroxide solution)]]> 26 28 29 28 30 34 34 34 37 33 N2(%) 47 50 50 53 55 63 60 57 64 50 <![CDATA[Izod impact strength of cantilever beam (kJ / m 2 )(soaked in toluene)]]> 27 29 31 30 31 39 38 38 45 38 N3(%) 49 52 53 57 56 72 67 63 78 69 <![CDATA[Izod impact strength of cantilever beam (kJ / m 2 )(acetone immersion)]]> 28 28 31 30 31 39 39 38 44 38 N4(%) 51 50 53 57 56 72 68 63 76 69 It can be observed from Table 2 that the tensile strength, flexural strength and Izod notched impact strength of Comparative Example 1 as a blank control are 54 MPa, 80 MPa and 55 kJ / m respectively. 2 Comparative Example 2 and Comparative Example 3 added 2.5 parts of nano-SiO 2 and 2.5 parts of hexagonal boron nitride nanotubes. Compared with comparative example 1, the addition of these two additives slightly improves the mechanical properties of the material. This is attributed to the nano-SiO 2 And hexagonal boron nitride nanotubes themselves have high strength and modulus. They are evenly dispersed in the PC / PBT system, partially restricting the movement of polymer molecular chains, and thus having a positive effect on the mechanical properties of the material. However, since there is no strong bond between these nanoparticles and the matrix material, the improvement in mechanical properties is not significant. In addition, the formula composition of Comparative Example 4 and Comparative Example 1 is exactly the same, the only difference is that Comparative Example 4 has undergone 50kGy radiation treatment. It can be seen from the data in Table 2 that after radiation treatment, the tensile strength of the material is increased from 54MPa to 60MPa, and the bending strength is increased from 80MPa to 87MPa. This shows that the radiation effect improves the compatibility between materials, and a cross-linked structure is generated between the molecular chains, thereby significantly improving the mechanical properties of the material.
[0027] Relative to Comparative Example 1, Examples 1-3 all added 2.5 parts of hexagonal boron nitride nanotubes to the materials, the difference being that the radiation doses they received were 200 kGy, 150 kGy and 50 kGy, respectively. By comparing the data, it can be found that with the increase in radiation dose, the tensile strength and bending strength of the PC / PBT alloy material both show a trend of gradual increase. This is because the increase in radiation dose leads to the generation of more active free radicals, which in turn promotes the cross-linking reaction between the molecular chains, making the material structure more compact. However, it is worth noting that with the increase in radiation dose, the cantilever beam notched impact strength of the material will show a downward trend. This is mainly due to the combined effect of nanoparticles and radiation that increases the crystallinity of the PC / PBT material. In addition, by comparing Comparative Example 5 and Example 3, it can be seen that under the same radiation dose, the introduction of hexagonal boron nitride into the PC / PBT alloy system can make the improvement of mechanical properties more obvious. This is due to the special planar hexagonal network structure of hexagonal boron nitride, which enables hexagonal boron nitride to form a stronger interaction with the polymer matrix, thus helping to improve the overall mechanical properties of the material.
[0028] Under the same radiation dose as Example 2, Example 4 added 3.5 parts of hexagonal boron nitride nanotubes. The experimental results show that the tensile strength, bending strength and cantilever beam notched impact strength of the material reached 74MPa, 110MPa and 58kJ / m² respectively, and the comprehensive mechanical properties were the best. This is because adding more hexagonal boron nitride nanotubes can more effectively prevent the expansion of cracks, so that the material can still maintain good mechanical properties in the case of defects or damage, thereby helping to improve the notched impact strength.
[0029] Furthermore, the chemical resistance of all comparative examples and embodiments was studied by immersion tests. Comparative Example 1 was not modified with nanoparticles and irradiated, and its tolerance range to 10% sulfuric acid, 10% sodium hydroxide, toluene and acetone was between 40% and 59%, which means that the tensile strength, flexural strength and cantilever beam notched impact strength of the material all dropped to less than 60% of the initial strength, and the mechanical properties decreased significantly. In contrast, in Example 4, hexagonal boron nitride nanotubes were introduced and irradiated with 150 kGy, and its tolerance range to 10% sulfuric acid, 10% sodium hydroxide, toluene and acetone was increased to between 62% and 89%. The tensile strength of Example 4 was still maintained at more than 46 MPa, the flexural strength was maintained at more than 83 MPa, and the cantilever beam notched impact strength was maintained at 37 kJ / m 2 The mechanical properties are still excellent.
Claims
1. A PC / PBT alloy material with high chemical resistance, comprising the following raw material components in parts by mass: PC resin: 55-80 parts PBT resin: 20-45 parts Compatibility agent: 1-5 parts Ester exchange inhibitor: 0.1-1 part Toughening agent: 1-10 parts Inorganic nanopowder: 1-5 parts Antioxidant: 0.1-1 part Lubricant: 0.2-1 part.
2. The PC / PBT alloy material with high chemical resistance according to claim 1, characterized in that: The PC resin is bisphenol A polycarbonate, and its melt flow index is 10-20 g / min under the test conditions of 300° C. / 1.2 kg; the intrinsic viscosity of the PBT resin is 0.8-1.2 dL / g.
3. The PC / PBT alloy material with high chemical resistance according to claim 1, characterized in that: The compatibilizer is a terpolymer of ethylene-methyl acrylate-glycidyl methacrylate; the toughener is an MBS resin, in which the core of the core-shell structure is styrene-butadiene rubber and the shell is a copolymer of styrene and methyl methacrylate.
4. The PC / PBT alloy material with high chemical resistance according to claim 1, characterized in that: The transesterification inhibitor is one or more of trimethyl phosphate, triphenyl phosphate, and diphenyl isooctyl phosphate.
5. The PC / PBT alloy material with high chemical resistance according to claim 1, characterized in that: The inorganic nano powder is hexagonal boron nitride nanotube.
6. The PC / PBT alloy material with high chemical resistance according to claim 1, characterized in that: The antioxidant is one or more of 1010, 1076 and 168; the lubricant is one or more of pentaerythritol stearate, calcium stearate and stearic acid amide.
7. The method for preparing a PC / PBT alloy material with high chemical resistance according to any one of claims 1 to 6, characterized in that: The preparation steps include PC / PBT alloy material preparation and radiation treatment.
8. The method for preparing a PC / PBT alloy material with high chemical resistance according to claim 7, characterized in that: The preparation of the PC / PBT alloy material is to stir and mix PC resin, PBT resin, compatibilizer, ester exchange inhibitor, toughening agent, inorganic nano powder, antioxidant and lubricant at high speed, add the mixture to the feeding port of a twin-screw extruder, melt extrude and granulate, the temperature of each section of the extruder is 240-270°C, the screw speed is 300-400rpm, and the screw aspect ratio is 40:
1.
9. The method for preparing a PC / PBT alloy material with high chemical resistance according to claim 7, characterized in that: The radiation treatment is to irradiate the PC / PBT alloy material with an electron beam generated by a high-energy accelerator, with a radiation dose of 50-200 kGy.
10. The PC / PBT alloy material with high chemical resistance according to any one of claims 1 to 6 is used in aerospace and energy industries.
Citation Information
Patent Citations
Nylon composite with excellent performance and low water absorbability and preparation method of nylon composite
CN104761889A
Scratch-resistant high-hardness PC / PBT composite material and preparation method thereof
CN114437530A